The Spanish interpretations of the Inca Empire in the colonial period - Anderle, Ádám (Acta Scientiarum Socialium, 2015)
The Spanish interpretations of the Inca Empire in the colonial period The essay renounces the traditional Spanish viewpoint of the conquista and instead proposes the introduction of the term historical compromise. The fact that Pizarro landed with 168 soldiers does not make the Spanish „conquest” conceivable from a military point of view. The author ascribes this compromise to the policy of Viceroy Toledo, and argues that it was also facilitated by a new historical approach. The pro-Inca Spanish viewpoint was replaced by a new one, which saw the Incas as conquerors and tyrants, and which enjoyed the support of the kurakas of the provinces (former Indian small states). In this view the Spanish appeared as liberators. The article also discusses Poma de Ayala’s interpretation, who imagined this (Habsburg-Tawantinsuyu) compromise with Indian hegemony. This compromise came to a crisis in the 18th century. It was signalled by the Inca restoration attempts, and then by the Túpac Amaru uprising, which fought for an independent Peru that was to be led by the kurakas.
Keywords: Inca Empire; kuraka-Spanish compromise; Habsburg-Tawantinsuyu; Viceroy Toledo; Túpac Amaru uprising